2008
DOI: 10.1016/j.jchemneu.2008.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular glutamate transporter 3-immunoreactive pericellular baskets ensheath a distinct population of neurons in the lateral septum

Abstract: The lateral septum (LS) plays a role in the adjustment of behavioral responses according to environmental demands. This is a complex integrative process wherein a variety of modulatory systems, i.e. cholinergic, dopaminergic and serotonergic projections forming pericellular baskets around LS neurons, are involved.Recently, vesicular glutamate transporter 3 (VGLUT3)-immunoreactive (-ir) structures outlining unlabeled somata and their proximal dendrites were described in the LS. However, the vesicular transporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 65 publications
(87 reference statements)
3
16
0
Order By: Relevance
“…The general pattern of calbindin (CB) staining observed in the LS was very similar to the findings of previous studies [4851]. CB-immunoreactive neurons were heterogeneously distributed throughout the LS.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The general pattern of calbindin (CB) staining observed in the LS was very similar to the findings of previous studies [4851]. CB-immunoreactive neurons were heterogeneously distributed throughout the LS.…”
Section: Resultssupporting
confidence: 87%
“…The presence of CR-immunoreactive neurons in the LS has been reported [51,81]. However, very few quantitative and comparative studies have been made with regard to the distribution of CR and its colocalization with GABA within the LS.…”
Section: Discussionmentioning
confidence: 99%
“…1B′ and C′) in situ hybridization techniques, we detect prominent labeled neurons for the glutamate transporter 3 (VGLUT3) mRNA in BST (Fig. 1; (Gras et al , 2002; Schafer et al , 2002; Herzog et al , 2004; Riedel et al , 2008); and 2) Using [H 3 ] D-aspartate retrograde tracing technique, numerous radiolabelled cell bodies were detected in the anterolateral and antero ventral BST (Csaki et al , 2000; Kocsis et al , 2003). This data taken together with our retrograde and anterograde labelings, and antidromic activation of BST neurons by VTA stimulation (Georges and Aston-Jones, 2002), give anatomical and physiological support for a glutamatergic projection from the BST to the VTA.…”
Section: Bst As a Hub Connecting Hippocampus Prefrontal Cortex Anmentioning
confidence: 93%
“…These observations suggested that VGLUT3 distribution in 5-HT terminals from the hippocampus was highly regionalized. In Figure 4h, two neurons from the lateral septum are covered by dense VGLUT3-positive pericellular baskets (Riedel et al, 2008;Shutoh et al, 2008). Only one of these neurons is surrounded by VMAT2 ϩ 5-HTϩVGLUT3 fibers.…”
Section: Vglut3 Colocalizes With Vmat2 and 5-ht But Rarely With Sertmentioning
confidence: 96%